The Oppression of Women in Maman Suherman's Re and Nawal El Saadawi's Woman at Point Zero : A Comparative Study - Hidayatus Sholihah (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri, 2023)
et,1/Mumtaz c.1